PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR FISIKA SISWA - Wahyuni, Sri; Nasar, Adrianus; Kaleka, Melkyanus (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2020)
This study aims to determine the effect of discovery learning learning model on student physics learning outcomes. The research subjects were 30 students of class X Madrasah Aliyah Muhammadiyah Riung in the 2019/2020 academic year. This type of research is quantitative. Ex-post facto research design that is causal. The data obtained are data on student learning outcomes in physics lessons. Data analysis carried out is normality test and t test. The results of hypothesis testing, obtained data t (countable) 9,403 the value of degrees of freedom is 29. The value of sig. (2-tailed) of 0.000. Significant value (sig. 2-tailed) 0.000 <0.05 then H0 is rejected and H1 is accepted (the proposed hypothesis is accepted). The results of these calculations can be concluded that there is a significant influence on the discovery learning model on the physics learning outcomes of class X Madrasah Aliyah Muhammadiyah Riung.